Polyclonal and monoclonal B lymphocytes response in HCV‐infected patients treated with direct‐acting antiviral agents. Issue 12 (9th August 2017) - Schiavinato, A.; Zanetto, A.; Pantano, G.; Tosato, F.; Nabergoj, M.; Fogar, P.; Piva, E.; Gambato, M.; Franceschet, E.; Floreani, A.; Farinati, F.; Burra, P.; et al.
Summary: Hepatitis C virus (HCV) chronic infection can be associated with extrahepatic manifestations such as mixed cryoglobulinaemia and lymphoproliferative disorders that are endowed with increased rates of morbidity and all‐cause mortality. In this study, we used flow cytometry to evaluate the effect of interferon‐free antiviral treatment on peripheral blood lymphocytes in HCV‐infected patients with or without associated lymphoproliferative disorders. Flow cytometry analysis of peripheral blood lymphocytes was performed at baseline and at the end of treatment. In HCV‐infected patients with lymphoproliferative disorders, we evaluated immunoglobulin (Ig) light chain κ/λ ratio variations as a measure of monoclonal B‐cell response to antiviral therapy. Healthy volunteers were enrolled as controls. A total of 29 patients were included, nine with and 20 without lymphoproliferative disorders. Sustained virological response was achieved in 29 of 29 patients. We observed a significant reduction in the B‐cell compartment (39% global reduction) in eight of nine HCV‐infected patients with lymphoproliferative disorders after viral clearance. We recognized the same trend, even if less pronounced, in HCV‐infected patients without lymphoproliferative disorders (9% global reduction). Among HCV‐infected patients with lymphoproliferative disorders, three showed an improvement/normalization of the immunoglobulin light chain ratio, whereas in the remaining six patients monoclonal B cells persisted to be clonally restricted even 1 year after the end of treatment. Our data show that DAAs treatment can be effective in reducing the frequency of pathological B cells in the peripheral blood of HCV‐infected patients affected by HCV‐associated lymphoproliferative disorders; however, monoclonal populations can persist after viral eradication.